Federacyjne koncepcje integracji europejskiej w programach wybranych partii na poziomie europejskim - Wiśniewska, Paula (Księgarnia Akademicka Publishing, 2020)
IDEAS FOR FEDERAL EUROPEAN INTEGRATION IN SELECTED PROGRAMS OF THE EUROPEAN PARTIES Why have European political parties decided to establish cooperation on a transnational level? What ideas for European integration do Europarties present in their political programs? What tools do they have at their disposal do they use them to influence the decision-making process in the European Union? What is the relationship between Europarties and political groups in the European Parliament? These are only a few questions which the author of the book attempts to answer in her research on the European People’s Party, the Party of European Socialists, the European Green Party, and the Alliance of Liberals and Democrats for Europe. With this end in view the author analyzes the election programs of the European People’s Party, the Party of European Socialists, the European Green Party, and the Alliance of Liberals and Democrats for Europe for the European Parliament elections between 1979 and 2019. Moreover, the author has individually and exhaustively interviewed members of the European Parliament and the Europarties leaders on developing manifests. choosing the European Commission president, the cooperation between the parties and the party groups. Additionally to the content analysis and qualitative interviews, the research makes use of the observation method in order to collect empirical data from the sessions of the political groups and the working groups in the European Parliament. The book is intended for European studies researchers and political scientists, but should also prove of interest to followers and practitioners of politics, especially those keen to learn what European parties are and how they work.